2004
DOI: 10.1111/j.1600-051x.2004.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal repair in dogs: effect of recombinant human bone morphogenetic protein‐12 (rhBMP‐12) on regeneration of alveolar bone and periodontal attachment

Abstract: The outcomes of this study suggest that rhBMP-12 may have significant effects on regeneration of the PDL. Additional preclinical evaluation is needed to confirm these initial observations prior to clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 44 publications
1
94
1
2
Order By: Relevance
“…A recent preliminary study in dogs compared rhBMP-12 with rhBMP-2 for the treatment of periodontal defects [129]. The results showed less bone and more functionally oriented PDL between the new bone and new cementum after BMP-12 treatment, contrasting with a more parallel fibre arrangement than BMP-2-treated defects.…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…A recent preliminary study in dogs compared rhBMP-12 with rhBMP-2 for the treatment of periodontal defects [129]. The results showed less bone and more functionally oriented PDL between the new bone and new cementum after BMP-12 treatment, contrasting with a more parallel fibre arrangement than BMP-2-treated defects.…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…These factors have historically been delivered in solution form, but this has significant limitations due to the short half-lives of these molecules in the body. In contrast, biomaterials-based delivery of these potent signaling molecules can lead to robust responses (Lee et al, 2000;Wikesjö et al, 2004;Chiu et al, 2013). For example, recombinant bone morphogenetic proteins in a collagen carrier are used clinically to promote healing of vertical alveolar bone defects and criticalsized bone defects, and in spinal fusions (McKay et al, 2007).…”
mentioning
confidence: 99%
“…23 Wang and colleagues also found evidence of a role for BMP-12 in differentiation by demonstrating that rhesus bone marrow mesenchymal stem cells could be induced to differentiate into tenocytes via BMP-12 gene transfection. 24 In a canine study, Wikesjo et al 25 demonstrated that rhBMP-12 in an absorbable collagen sponge was able to form a functionally oriented periodontal ligament bridging the gap between newly formed bone and cementum. Together, these data strongly support a role for BMP-12/GDF-7 in tenocyte differentiation and matrix remodeling.…”
Section: Discussionmentioning
confidence: 99%